(3GdaJhI hGdTYQ hGdYgOs - (3eMeO Hf Ydj GdOGdjs ((3eMeO HgGA GdOjf GdLGHQi GdMSjfi s)
(3ChdgG (B:s
(3CeG HYO abO Qhi Yf eMeO Hf GdSjO Ydi GdOGdi eUfa gPg GdaJhg heYQaI GdWQjb hHMGQ GdMbGFb hCQcGf GdTQjYI s
(3BNQgG (B:s
(3hGJbhG Gddg Ef Gddg TOjO GdYbGHJeJ GdeSGFd hGddg Gdehab ddMeO hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B89) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs